Research in social movements, conflicts and change. Vol. 27 - Coy, Patrick G. (Amsterdam ; Oxford : Elsevier JAI, 2007)
This volume of "Research in Social Movements, Conflicts and Change" contains a strong collection of theoretically rich and data-driven papers, which address a series of interrelated questions that are at the forefront of todays social movement scholarship. For example, political opportunity theory has been justly criticized for privileging structure over agency, politics over culture, and for failing to adequately specify how political opportunities differ for social movements in democracies vs. in non-democracies.In this volume, political opportunity theory receives careful, empirically-informed correctives from a number of quarters. In addition, a synthesis is achieved between nonviolent action scholarship and the contentious politics school of research. Equally important, the roles of collective identities, ideologies, identity talk, art, biographies, social networks, police repression, and participation pathways are analyzed within the context of social movements in the United States, Mexico, the Netherlands, India, Brazil, Northern Ireland, and in various non-democracies. This is that too rare collection which when taken together builds bridges between scholarship on social movements and on social conflicts, and in the process makes theoretical advances in each area in much needed yet creative ways. In that way, this volume carries on the distinguished tradition of the Research in Social Movements, Conflicts and Change series.
From civil war to civil rights and back again: The interrelation of rebellion and protest in Northern Ireland, 1955-1972 / Gregory M. Maney -- Social movement participation and the "timing" of involvement: The case of the Northern Ireland civil rights movement / Lorenzo Bosi -- Police knowledge revised: Insights from the policing of the civil rights movement in Northern Ireland / Gianluca De Fazio -- Rethinking nonviolent action and contentious politics: Political cultures of nonviolent opposition in the Indian independence movement and Brazil's landless workers movement / Sean Chabot and Stellan Vinthagen -- A long, hard slog: Political opportunities, social networks and the mobilization of dissent in non-democracies / Maryjane Osa and Kurt Schock -- Strategic women, elite advocacy and insider strategies: The women's movement and constitutional reform in Wales / Paul Chaney -- Ideology, organization, and biography: The cultural construction of identity talk amond progressive activists in Hartford, Connecticut / Stephen Valocchi -- Art and identity in Mexican and Chicano social movements / Edward J. McCaughan -- New frontiers for identity politics? The potential and pitfalls of patient and civic identity in the Dutch patients' health movement / Jan Willem Duyvendak and Trudi Nederland -- Paths to participation: A profile of the civil rights-era Ku Klux Klan / David Cunningham.
Includes bibliographical references.
Description based on print version record.
Keywords: Social movements; Social conflict; Social psychology; Social issues & processes; Social Science -- Sociology -- General; Electronic books